Age-related differences in eating location, food source location, and timing of snack intake among U.S. children 1-19 years - Gina L. Tripicchio; Christina M. Croce; Donna L. Coffman; Cameron Pettinato; Jennifer O. Fisher (BMC, 2023)
Abstract Background Snacking is nearly universal and contributes significant energy to U.S. children's diets. Little is known, however, about where and when snacking intake occurs and if such patterns change with age. This research evaluated age-related differences in eating location, food source location, and timing of snacking among U.S. children aged 1-19 years (y). Methods A cross-sectional analysis of snacking among 14,666 children in the 2007-2018 U.S. National Health and Nutrition Examination Survey was conducted using a single 24-hour dietary recall. Snacking was participant-defined and included all eating occasions outside of meals. Linear regression and analysis of covariance were used to examine the effects of age (toddler 1-2 y, preschooler 3-5 y, school-age 6-11 y, adolescent 12-19 y) on the percentage of daily snack energy consumed by eating location (at home vs. away from home), food source location (grocery store, convenience store, school/childcare, restaurant, from someone else (i.e. "socially"), and other), and time of day (morning, 6am-12pm; early afternoon, 12pm-3pm; late afternoon/afterschool 3pm-6pm; evening 6pm-9pm, late-night 9pm-12am, and overnight 12am-6am). Results On average, U.S. children consumed most of their daily snacking energy at home (71%), from foods and beverages obtained from grocery stores (75%), and in the late afternoon/afterschool (31%). Toddlers and preschoolers consumed a greater percentage of their daily snack energy during the morning hours compared to school-age children and adolescents (both p < 0.001); school-age children consumed the most in the evening (27%, p < 0.001), and adolescents consumed the most in the late-night period (22%, p < 0.001). Age-related increases were seen in the percentage of daily snacking energy eaten outside the home (p < 0.001), and obtained socially (p < 0.001), from restaurants (p < 0.001), and convenience stores (p < 0.001). Conclusion Findings reveal age-related differences in eating location, food source location, and timing of snack intake among U.S. children aged 1-19 y. Younger children consume a greater percentage of snacking calories in the morning and at home relative to older children. School-age children and adolescents show greater snacking in the evening and at night and from foods obtained and eaten outside the home. Efforts to promote healthy snacking behaviors among children should consider developmental differences in snacking patterns.